Intangible capital in the Finnish business sector, 1975-2005 - Jukka Jalava; Pirkko Aulin-Ahmavaara; Aku Alanen (The Research Institute of the Finnish Economy (ETLA), 2007)
This paper is the first effort to analyze the intangible investments of the Finnish non-financial business sector in 1975–2005 with a heretofore unseen scope of intangible investments in line with the definition of Corrado, Hulten and Sichel (2005, 2006). Not only GDP but also investments have become more weightless as the importance of scientific innovative property and economic competencies has increased. In 2005 Finnish business intangible investments amounted to 14.2 billion euro, which was 9 per cent in relation to (unrevised) GDP. Our results imply higher investments rates and lower labor shares than traditionally thought. Comparing our new results with SNA93-type growth decompositions we found that our revision increased the average growth rate of labor productivity by 0.48 percentage points in 1995–2000 and 0.06 percentage points in 2000–2005. Capitalizing intangible investments decreased the measure of our ignorance by 0.12 percentage points in 1995–2000 and 0.45 in 2000–2005. A shift to new, intangible, investments with higher marginal products than traditional capital has taken place. It is not any longer solely a matter of how much is invested, but what it is firms invest in.
Keywords: 330; intangible capital; growth accounting; productivity; Intangibles Gut; Forschung; Immaterialgüterrechte; Kompetenz; Investition; Arbeitsproduktivität; Finnland